a Descriptive Analysis of Self-Efficacy and Positive Perception Toward Headaches in Young Adults: ANALISIS DESKRIPTIF EFIKASI DIRI DAN PERSEPSI POSITIF TERHADAP NYERI KEPALA DEWASA MUDA - Nona Suci Rahayu; Siti Rahmah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Headache is a common complaint among individuals in their productive age, particularly young adults. Management often remains limited to pharmacological treatment, despite the potential benefits of a restorative biopsychosocial approach, which may enhance outcomes by strengthening positive perception (well-being) and self-efficacy.This study aimed to descriptively examine the association between positive perception and self-efficacy with the intensity level of headache in young adults.This research employed a descriptive observational design with a quantitative approach. The study subjects consisted of adult patients (≥18 years) experiencing primary headaches such as migraine or tension-type headache for ≥3 months and who were willing to complete the questionnaires. Data were collected at the Neurology Clinic of the Mother and Child Hospital in Banda Aceh during April–June 2025. The instruments used included the Numeric Rating Scale (NRS) for pain intensity, the WHO-5 Well-Being Index for psychological well-being, and the Pain Self-Efficacy Questionnaire (PSEQ) for pain-related self-efficacy. The results showed that most respondents were young adult women with student academic backgrounds. Although the majority experienced moderate pain, they generally demonstrated good levels of self-efficacy and positive perception. These findings support the need for non-pharmacological interventions based on the biopsychosocial model in managing recurrent headaches, especially among academically active young adults.